Homozygotic intronic GAA mutation in three siblings with late-onset Pompe's disease Mutação homozigótica intrônica no gene GAA em três irmãos com doença de Pompe de início tardio - Anderson Kuntz Grzesiuk; Sueli Mieko Oba Shinjo; Roseli da Silva; Marcela Machado; Marcial Francis Galera; Suely Kazue Nagahashi Marie (Arquivos de Neuro-Psiquiatria)
Pompe's disease (PD) is a metabolic myopathy caused by the accumulation of lysosomal glycogen, secondary to acid α-glucosidase (GAA) enzyme deficiency. Childhood and late-onset forms are described, differing by the age of onset and symptoms. In this study were analyzed affected siblings with Pompe's disease (PD) and their distinct clinical and pathological presentations. METHOD: Diagnosis was performed by the clinical presentation of limb-girdle dystrophies and respiratory compromise. Confirmatory diagnoses were conducted by muscle biopsy, GAA activity measurement and by GAA gene genotyping. RESULTS: The findings suggested muscular involvement due to GAA deficiency. GAA genotyping showed they are homozygous for the c.-32-3C>A mutation. CONCLUSION: Herein we reported a family where three out of five siblings were diagnosed with late-onset PD, although it is a rare metabolic disease inherited in an autossomal recessive manner. We emphasize the importance of including this presentation within the differential diagnoses of the limb-girdle dystrophies once enzyme replacement therapy is available. A doença de Pompe (DP) é uma miopatia originada do acúmulo lisossomal de glicogênio, devido à deficiência da enzima α-glicosidase ácida (GAA), sendo descritas formas de inicio precoce e tardio. Neste estudo analisamos retrospectivamente o perfil clinico e patológico de 3 irmãos portadores de doença de Pompe de inicio tardio. MÉTODO: O diagnóstico foi realizado mediante apresentação clinica de distrofia de cinturas associado a comprometimento respiratório, sendo confirmado por biópsia muscular e análise da atividade e genotipagem da GAA. RESULTADOS: Os exames clínicos e laboratoriais demonstram envolvimento muscular devido à deficiência da GAA, com uma mutação c.-32-3C>A em homozigose. CONCLUSÃO: Relatamos os aspectos clínicos e laboratoriais de 3 irmãos afetados por doença de Pompe de início tardio. Enfatizamos a importância de incluir esta patologia no diagnóstico diferencial das distrofias de cinturas, uma vez que para esta patologia específica existe a possibilidade terapêutica através de reposição enzimática.